Mechanisms and spatial spillover effects of science and technology financial ecosystem on carbon emission reduction from multiple perspectives: evidence from China - Jinyue Zhang; Zhenglin Sun (Humanities & Social Sciences Communications)
Abstract When the global community is actively combating climate change and advancing the sustainable development process, the crucial role of the science and technology finance ecosystem (STFE) in carbon reduction has not been fully explored. In this paper, an evaluation system for the STFE is constructed from two dimensions, namely the “macro-environment subsystem” and the “micro-community subsystem”. From a new perspective of the STFE, it is introduced into the endogenous economic growth model, and combined with the STIRPAT model, a theoretical model of the carbon emission reduction effect of the STFE is explored. Based on the panel data of 284 prefecture-level cities from 2011 to 2020, the dynamic spatial Durbin model is adopted to examine the spatial spillover effect of the STFE on carbon emission reduction and its influencing mechanism. The results are as follows: (1) STFE in China has a spatial imbalance with a pattern of “high in the east and low in the west”. Total factor carbon productivity (TFCP) shows a spatial distribution pattern where “block distribution prevails in mid and low-level cities, supplemented by point distribution in high-level cities”. (2) Local STFE can facilitate local city carbon emission reduction; however, the development of local STFE is harmful to carbon emission reduction in neighboring cities, resulting in the negative externality of the “beggar-thy-neighbor” spatial spillover effect. (3) Heterogeneity analysis indicates that only the STFE in the eastern region is harmful to the improvement of the carbon emission reduction level in neighboring regions, while the positive spatial spillover effect of the STFE carbon emission reduction effect is more prominent in non-resource cities and high-financial-development areas. (4) The negative spatial spillover effect of the development of local STFE on carbon emission reduction in neighboring areas operates through the mechanisms of green technology innovation, human capital siphoning, the digital divide in informatization development, and the competitive exclusion in financial resource allocation. These conclusions not only provide a new research perspective and complementary empirical evidence but also offer a practical guideline for strengthening STFE and facilitating the growth of a low-carbon economy.